PROGRAM SEDERHANA SISTEM PENGENALAN WAJAH MENGGUNAKAN FUNGSI JARAK - Abdul Fadlil (Universitas Ahmad Dahlan, 2006)
Over the years, face recognition ones of biometric characteristic has attracted attention of many researchers and scientists. Many efforts has been done to built an automatic system capable of recognizing faces with several different techniques. The simple program for face recognition has been developed. The purpose of this program is to compare efectifity two simple distance functions namely Manhattan (L1) and Euclidean (L2) as classifier for face recognition system. In this research, system is trained and tested using dataset images of the five persons with different expresion faces. The results of our experiments show that the system could be more accurate from 95% for Manhattan distance function (L1) to be 100% for Euclidean distance function (L2).